BIBLIOMETRIC ANALYSIS OF SECTORAL SHIFTS AND INVESTOR BEHAVIOR - Judijanto, Loso (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This study explores the dynamics of investor behavior, investments, and the influence of financial markets through a bibliometric analysis using VOSviewer. The keyword mapping reveals